2023
DOI: 10.1021/acsnano.2c10737
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Layer Transfer of 2D Materials for Monolithic 3D Electronic System Integration: Review and Outlook

Abstract: Two-dimensional materials (2DMs) have attracted a great deal of interest due to their immense potential for scientific breakthroughs and technological innovations. While some 2D transition metal dichalcogenides (TMDC) such as MoS2 and WS2 are considered as the ultimate channel materials in unltrascaled transistors as replacements for Si, there has also been increasing interest in the monolithic 3D integration of 2DMs on the Si CMOS platform or in flexible electronics as back-end-of-line transistors, memory de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 121 publications
0
27
0
Order By: Relevance
“…92 Although huge progress has been made in the large area 2D layer transfer technology recently, several obstacles still mar the three main steps of the transfer process, namely, low peeling yields; formation of cracks, wrinkles, or bubbles during the subsequent attachment to the target; and presence of polymer residues and incomplete release from carrier. 93 Hence, the development of robotic/automated systems (detacher and bonder) with precise control over detaching−attaching forces and peel-front propagation can be extremely useful in alleviating these issues. Automated detachers can help in the process by avoiding mechanical bending of the 2D material layer/film, which minimizes consequent crack propagation and also improves peeling yields.…”
Section: D Transfer Modulesmentioning
confidence: 99%
“…92 Although huge progress has been made in the large area 2D layer transfer technology recently, several obstacles still mar the three main steps of the transfer process, namely, low peeling yields; formation of cracks, wrinkles, or bubbles during the subsequent attachment to the target; and presence of polymer residues and incomplete release from carrier. 93 Hence, the development of robotic/automated systems (detacher and bonder) with precise control over detaching−attaching forces and peel-front propagation can be extremely useful in alleviating these issues. Automated detachers can help in the process by avoiding mechanical bending of the 2D material layer/film, which minimizes consequent crack propagation and also improves peeling yields.…”
Section: D Transfer Modulesmentioning
confidence: 99%
“…The stacking ability of two-dimensional (2D) materials allows for the sequential combination of different 2D materials to form van der Waals (vdW) heterojunction, leveraging their no chemical bonds on the surface and weak vdW forces between adjacent layers. , Exploiting this vdW heterojunction, it becomes possible to integrate sensing, storage, and computation within a single transistor, eliminating delays and reducing energy consumption associated with data transmission, thus enhancing the performance of microneural network system. ,, Previous research has demonstrated the potential of neural networks based on a 2D material vdW heterojunction transistor. For instance, Zhou et al utilized BP/WS 2 /h-BN vdW heterojunction combined with neural networks to construct a multifunctional 2D disparity hardware device for motion detection and recognition .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared with substrate supported material, suspended 2D materials yield superior advantages in terms of deformation and transduction mechanisms for acoustic devices. [33] Upon eliminating the interaction with the substrate (such as mechanical and thermal disruption), the substrate no longer hinders the material's vibration, deformation, and recovery process, thereby enabling the suspended material to respond independently and realize its full potential for high-performance acoustic devices. [29] In this review, we summarize the progress of acoustic devices based on suspended 2D materials and their composites, emphasizing the advantageous properties of suspended 2D membranes and related outstanding device performance (Figure 1).…”
Section: Introductionmentioning
confidence: 99%